Immune Responses to a Recombinant Glycoprotein E Herpes Zoster Vaccine in Adults Aged 50 Years or Older. (26th February 2018) - Cunningham, Anthony L; Heineman, Thomas C; Lal, Himal; Godeaux, Olivier; Chlibek, Roman; Hwang, Shinn-Jang; McElhaney, Janet E; Vesikari, Timo; Andrews, Charles; Choi, Won Suk; Esen, Meral; Ikematsu, Hideyuki; et al.
Abstract: Background: The herpes zoster subunit vaccine (HZ/su), consisting of varicella-zoster virus glycoprotein E (gE) and AS01B Adjuvant System, was highly efficacious in preventing herpes zoster in the ZOE-50 and ZOE-70 trials. We present immunogenicity results from those trials. Methods: Participants (ZOE-50: ≥50; ZOE-70: ≥70 years of age) received 2 doses of HZ/su or placebo, 2 months apart. Serum anti-gE antibodies and CD4 T cells expressing ≥2 of 4 activation markers assessed (CD4 2+ ) after stimulation with gE-peptides were measured in subcohorts for humoral (n = 3293) and cell-mediated (n = 466) immunogenicity. Results: After vaccination, 97.8% of HZ/su and 2.0% of placebo recipients showed a humoral response. Geometric mean anti-gE antibody concentrations increased 39.1-fold and 8.3-fold over baseline in HZ/su recipients at 1 and 36 months post-dose 2, respectively. A gE-specific CD4 2+ T-cell response was shown in 93.3% of HZ/su and 0% of placebo recipients. Median CD4 2+ T-cell frequencies increased 24.6-fold (1 month) and 7.9-fold (36 months) over baseline in HZ/su recipients and remained ≥5.6-fold above baseline in all age groups at 36 months. The proportion of CD4 T cells expressing all 4 activation markers increased over time in all age groups. Conclusions: Most HZ/su recipients developed robust immune responses persisting for 3 years following vaccination. Clinical Trials Registration: NCT01165177; NCT01165229. Abstract : The herpes zoster subunit vaccine, consisting of varicella-zoster virus glycoprotein E and the AS01B Adjuvant System, stimulated specific antibody and CD4 T-cell responses in >90% of recipients which, in most, persisted for the 36-month duration of the study.